2017
DOI: 10.5812/ircmj.43554
|View full text |Cite
|
Sign up to set email alerts
|

Ethical Leadership and Organizational Climate: The Experience of Iranian Nurses

Abstract: Background: As a legitimate and credible role-model, the ethical nurse leader engages in the proper structuring of the workplace and plays a significant role in improving the organizational climate. Despite the importance of the subject, no studies have yet examined the effect of ethical nursing leadership in improving organizational climates in Iran. Objectives: The study was conducted to explore the ways for improving organizational climate through ethical leadership from Iranian nurses perspective. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 34 publications
0
6
0
1
Order By: Relevance
“…Hospital managers, a factor that in most studies received a positive evaluation, need to improve teamwork, investing in enhancements in the workplace and showing their willingness to improve the organizational climate and assistance 39 . The appreciation of professional categories supports work diversification and the creation of respectful relationships, which encourages team performance 34 .…”
Section: Discussionmentioning
confidence: 99%
“…Hospital managers, a factor that in most studies received a positive evaluation, need to improve teamwork, investing in enhancements in the workplace and showing their willingness to improve the organizational climate and assistance 39 . The appreciation of professional categories supports work diversification and the creation of respectful relationships, which encourages team performance 34 .…”
Section: Discussionmentioning
confidence: 99%
“…This behavior and practice can be effective in promoting effective health care for patients and individuals. [ 18 19 20 21 22 23 24 ]…”
Section: Discussionmentioning
confidence: 99%
“…They have suggested that an employee-oriented and egalitarian management style in the organizations would positively affect the employees' thoughts on the working atmosphere of the organization. Esmaelzadeh, Abbaszadeh, Borhani, and Peyrovi (2017) stated that ethical leaders improved the organizational climate composed of job environment, communication climate and ethical climate from three dimensions. They expressed that ethical leaders built an environment in which organizational definition, trust, and solidarity are ensured by standardizing working conditions among employees and increasing employees' interest in the environment.…”
Section: Discussionmentioning
confidence: 99%